Trap parameters of dosimetric glow peaks of the CaF2:Tm compounds (TLD-300). (November 2015) - Molina, P.; Ortega, F.; Marcazzó, J.; Santiago, M.; Spano, F.; Caselli, E.
Abstract: The kinetic parameters of dosimetric peaks of CaF2 :Tm (TLD-300) were found by employing a kinetics model derived from differential equations describing the carriers traffic but without resorting to the quasi-equilibrium approximation. Since both shape and position of glow peaks were observed not to change with dose, retrapping rates have been assumed negligible compared to rates of thermal release of electrons. The reported results show that the quasi-equilibrium approximation does not hold, an approximation used for derivation of first order kinetics, which is the kinetics employed so far for analyzing glow curves of the TLD-300. Highlights: Dosimetric peaks of the CaF2 :Tm compounds (TLD-300). Trap parameters found by glow curve deconvolution. Employed kinetics derived without resorting to the quasi-equilibrium approximation.